Cinema, formação, invenção de si e do mundo : o que pode o cinema? - Fonseca, Danuza de Oliveira (2015)
This research aims to study the ways of life today using Cinema as a device of an invention of the self and of the world. Cinema making lines of escape in teaching; cinema as a problem-solving vector of contemporary life, as weel as a vehicle that can promote a new way of thinking (DELEUZE, 1990), inquiring about the dogmatic images of thought, enabling the production of other subjects. Still, this study attempts to systematize theoretical basis about the formation and production of the subjectivity in the midst of the contemporary cultural ethos based on some of the assumptions of the philosophers Gilles Deleuze and Peter Pál Pelbart to guide this work. In this dissertation, we will try to discuss what can cinema do as a creative power of inventive thought; reflect on its potencial as a device that lets you create lines of scape and other experimentations, amid a capitalist modus vivendi (consumption habits, worldview, relationships, ways of living etc.) which wants to homogenize everyting. From these aspects, we will discuss formation by way of inventive learning (KASTRUP, 2003) throught Cinema, believing in the potential of film works as strategic pedagogical devices to promote a problem-based education. Hence, we advocate that a pedagogical practice that considers movies in forcing thought, pursues expansion of the autonomy and a philosophical aesthetic exercise, which can cause a kind of thinking that is able to build new worlds and (re) think our position on it. We argue that this work can contribute to the questioning of established ways of living, promoting subjectivity of aesthetic and political contributions via cinema, not to mention helping us problematize how films have been read by students and teachers, and especially when we assume to promote an inventive formation. In this research we discuss modes of formation and how cinema can be an important tool in this formation, exercising thinking, without reducing the use of movies to a didactic and methodological resource for teaching and learning, but mainly as opening opportunities of new educational practices, and then other modes of subjectivations in the contemporary world.